EKSISTENSI KOMISI YUDISIAL DALAM SISTEM KETATANEGARAAN INDONESIA BERDASARKAN UNDANG-UNDANG DASAR 1945 - jufri zulfan (ASAS Law Journal, 2023)
One the most important effort to be mode in order to maintain the honor and dignity of judges in the judiciary in a country is to convene or create a power that can supervise it which itself is separate from the supervised authority or an external party from the supervised party. The judicial commission was formed in order to maintain the authority and dignity of judges, as well as to make preventive efforts so that judges do not violate the code ethics that could undermine public trusrt in them. The judicial commission as the externally supervises judges as stipulated by the 1945 Constitution makes it necessary to work extra and be careful. The position and function of the Judicial Commission which is clear and has legal consequences but is only considered as a Supporting Institution and is not comprehensive because of its function object. From this background, the following problems can be formulated: What is the exixtence of the Judicial Commission in the Indonesian constitutional system based on the 1945 Constitution?, What is the function of the Judicial Commission in the Indonesian constitutional system based on the 1945 Constitution ?. From this study the authors conclude that the existence of the Judicial Commission as a state institution is mentioned in the 1945 Constitution is mentioned in the 1945 Constitution Article 24A paragraph (3) and Article 24B which explains the authority of the Judicial Commission, that the Judicial Commission has the authority to nominate candidates for Supreme Court judges, and uphold honor, nobility dignity, as well as the behavior of judges and finally the Judicial Commission is independent, has a legal basis and constitutionally the Judicial Commission is not a Supporting Institution in nature but equal to other state institutions and considering that constitutionally Supporting Institution are completely unknown. Seeing the existence and functions of the Judicial Commission which has been clearly stated in the 1945Constitution and has the authority which has also been celearly defined in the 1945 Constitutio, and added to Law Number 22 of 2004 concerning the Judicial Commission and Law Number 18 of 2011 concerning Amandments to Law Number 22 of 2004 concerning the Judicial Commission, the supervisory function carried out by the Judicial Commission is based on law which gives legimacy to its existence as one of the state administrators (state institutions) and the functions carried out by the Judicial Commission and its function as supervisor of judges and enforce of the honor of nobility and the code of ethics of judge, and this was indeed different before the Judicial Commission was held, precisely during the old order and the new order. The Judicial Commission was held due to the emergence of distrust and the great hope for the purity and cleanness of the judicial power from violations and is also inseparable from the judges themselves, the presence of the Judicial Commission has only been realized after everal years of reform in this country, so it is hoped that the presence of the Judicial Commission will be true-can actually maintain and keep it controlled and trusted by the public.